Porous carbon fiber felt, fragrance material and fragrance
By using porous carbon fiber felts with an average pore size of 1 to 1.5 nm and inorganic microporous material coating, the problem of uneven fragrance release and short duration in the fragrance sustained release technology is solved, and the long-lasting and stable release of fragrances and fragrances is achieved. and the service life is improved.
Patent Information
- Application Number
- CN202411322332.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The existing fragrance sustained release technology has the problems of uneven fragrance release and short duration, which cannot meet the needs of consumers.
Porous carbon fiber felt with an average pore size of 1 to 1.5 nm and a total pore capacity of 1 to 1.2 cm3/g was used, and ultra-microporous structure was formed by activator and heat treatment. Combined with inorganic microporous materials and sol coating, fragrance and The sustained release effect of fragrance.
It achieves the long-lasting and stable release of spices and fragrances, improves service life and use effect, and ensures even and sustained release of fragrance.
Smart Images

Figure CN119243466A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fragrance sustained release, and in particular to a porous carbon fiber felt, a fragrance material and a fragrance. Background Art
[0002] With the rapid development of the automobile industry and the increasing demand for in-car comfort, car fragrances have gradually become a popular product on the market. However, most existing fragrances have problems such as uneven fragrance release and short duration, which cannot meet the needs of consumers. Therefore, it is particularly important to develop a fragrance with a slow-release effect.
[0003] The existing fragrance slow-release technologies are as follows: (1) spraying water perfume in the car or indoors regularly through a spray bottle; (2) coating the surface of the filter element with perfume or fragrance essential oil (the filter element is installed in the car or in the home air conditioner); (3) placing the fragrance stick directly on the air outlet of the blower or fan; (4) The fragrance slow-release generally involves infiltrating the fragrance essential oil into a porous ceramic plate or rod, and using the air flow to emit the fragrance to the environment. The ceramic rod is divided into a surface porous layer, a diffusion layer and a sealing layer. It is generally composed of aluminum oxide, silicon oxide or a composite material. The existing fragrance slow-release technologies have a short fragrance slow-release time, and as the ceramic plate is used for a longer time, the fragrance gradually changes from being too strong at the beginning due to the excessive amount of essential oil released to becoming very light in the later stage of use, that is, the above-mentioned ceramic plate cannot achieve uniform and continuous fragrance slow-release.
[0004] Traditional fragrance materials mostly use carriers with poor adsorption properties, and the pore structure (micropores, mesopores, macropores) has a wide distribution range, resulting in uneven fragrance release and short duration. Porous carbon fiber felt and molecular sieves have great potential in the field of adsorption and sustained release due to their highly developed microporous structure and excellent adsorption performance.
[0005] In view of this, this application is filed. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a porous carbon fiber felt, a fragrance material and a fragrance. The porous carbon fiber felt can effectively control the sustained release effect of spices and flavors, so that the spices and flavors are released in a long-lasting and stable manner, effectively improving the service life and use effect.
[0007] To achieve the above-mentioned purpose, the first aspect of the present application provides a porous carbon fiber felt, the average pore size of which is 1 to 1.5 nm and the total pore volume is 1 to 1.2 cm 3 / g, air permeability ≤8s, surface oxygen group content 0.6~2.1wt%;
[0008] The porous carbon fiber felt has ultra-micropores, the pore size of the ultra-micropores is 0.3-1.2 nm, and the capacity of the ultra-micropores is 0.4-0.5 cm 3 / g.
[0009] A second aspect of the present application provides a method for preparing a porous carbon fiber felt, comprising the following steps:
[0010] The activated carbon fiber felt is immersed in an activator, dried, and heat-treated to obtain a porous carbon fiber felt;
[0011] The activator comprises zinc chloride solution and potassium hydroxide solution; the mass ratio of the zinc chloride solution to the potassium hydroxide solution is 1:(0-1);
[0012] The heat treatment is performed in a nitrogen atmosphere, a mixed atmosphere of nitrogen and carbon dioxide, or a mixed atmosphere of nitrogen and hydrogen.
[0013] As an embodiment of the present application, the activated carbon fiber felt has a thickness of 1 to 3 mm and a density of 0.5 to 0.15 g / cm 3 , specific surface area 1000~1200m 2 / g, average pore size 1.5~2nm, water absorption pore volume 0.85~0.95cm 3 / g.
[0014] As an embodiment of the present application, the mass concentration of zinc chloride in the zinc chloride solution is 2-8%.
[0015] As an embodiment of the present application, the mass concentration of potassium hydroxide in the potassium hydroxide solution is 2-8%.
[0016] As an implementation scheme of the present application, the temperature of the heat treatment is 950 to 1200° C., and the heat treatment time is 2 to 4 hours.
[0017] As an implementation scheme of the present application, the volume ratio of nitrogen to carbon dioxide is (80-95):(5-20).
[0018] As an implementation scheme of the present application, the volume ratio of nitrogen to hydrogen is (80-95):(5-20).
[0019] A third aspect of the present application provides an application of a porous carbon fiber felt in preparing fragrance.
[0020] The fourth aspect of the present application provides a fragrance material, comprising a porous carbon fiber felt and a fragrance loaded inside the porous carbon fiber felt, wherein the loading amount of the fragrance is 58 to 72 g / m 2 ;
[0021] The porous carbon fiber felt is the porous carbon fiber felt described above.
[0022] A fifth aspect of the present application provides a fragrance, comprising a fragrance material and a coating located on at least one surface of the fragrance material, wherein the coating comprises an inorganic microporous material and a sol;
[0023] The solvent includes alumina sol or silica sol;
[0024] The inorganic microporous material includes at least one of 3A molecular sieve, 5A molecular sieve, X-type zeolite, ZSM series molecular sieve, 13X molecular sieve, activated carbon molecular sieve, and activated carbon fiber powder;
[0025] The fragrance material is the fragrance material described above.
[0026] As an embodiment of the present application, the thickness of the coating layer is 5 to 50 μm.
[0027] As an embodiment of the present application, the mass ratio of the inorganic microporous material to the sol is (1-20): (80-99).
[0028] A sixth aspect of the present application provides a fragrance, including a filter element and fragrance materials located on both sides of the filter element, wherein the fragrance materials are the fragrance materials described above.
[0029] The beneficial effects of the present invention are as follows: the porous carbon fiber felt of the present invention has a rich pore structure and extremely low surface oxygen content groups, low air permeability, and has a pore size of 0.3-1.2 nm and a capacity of 0.4-0.5 cm 3 / g ultra-micropores, the porous carbon fiber felt has excellent hydrophobicity, and at the same time has a certain degree of graphitization, has excellent affinity with spices and flavors, can effectively inhibit the rapid desorption of spices and flavors, and can slowly and evenly control the fragrance desorption rate by using the small hole confinement effect, effectively control the sustained release effect of spices and flavors, make the spices and flavors release lastingly and stably, and effectively improve the service life and use effect. Similarly, using microporous inorganic molecular sieve material coating on the surface of porous substrates can also achieve similar sustained release effects by using its small hole confinement effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the fragrance material of the present invention.
[0031] Figure 2 FIG. 4 is a schematic diagram of the structure of another fragrance material of the present invention.
[0032] Figure 3 This is a diagram showing the sustained release effect of the fragrance of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0037] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0038] The present invention provides a porous carbon fiber felt having an average pore size of 1 to 1.5 nm and a total pore volume of 1 to 1.2 cm 3 / g, air permeability ≤8s, surface oxygen group content 0.6~2.1wt%;
[0039] The porous carbon fiber felt has ultra-micropores, the pore size of the ultra-micropores is 0.3-1.2 nm, and the capacity of the ultra-micropores is 0.4-0.5 cm 3 / g.
[0040] The porous carbon fiber felt of the present invention has a rich pore structure and extremely low surface oxygen content groups, low air permeability, and has a pore size of 0.3-1.2 nm and a capacity of 0.4-0.5 cm 3 / g of ultra-fine pores, the porous carbon fiber felt has excellent hydrophobicity and a certain degree of graphitization, and has excellent affinity with spices and flavors, and can effectively inhibit the rapid desorption of spices and flavors. The small hole confinement effect can slowly and evenly control the fragrance desorption rate, effectively control the sustained release effect of spices and flavors, and make the spices and flavors release lastingly and stably, effectively improving the service life and use effect.
[0041] An embodiment of the present application provides a method for preparing a porous carbon fiber felt, comprising the following steps:
[0042] The activated carbon fiber felt is immersed in an activator, dried, and heat-treated to obtain a porous carbon fiber felt;
[0043] The activator comprises zinc chloride solution and potassium hydroxide solution; the mass ratio of the zinc chloride solution to the potassium hydroxide solution is 1:(0-1);
[0044] The heat treatment is performed in a nitrogen atmosphere, a mixed atmosphere of nitrogen and carbon dioxide, or a mixed atmosphere of nitrogen and hydrogen.
[0045] The present invention prepares the above-mentioned porous carbon fiber felt by activating activated carbon fiber and then performing heat treatment. A special activator and a special atmosphere treatment are used to form a multi-level ultra-microporous, microporous and mesoporous carbon fiber pore structure, which has excellent pore capacity and can evenly accommodate dispersed spices and flavors. The small pore confinement effect can slowly and evenly control the fragrance desorption rate. At the same time, the porous carbon fiber felt has a certain degree of graphitization, has excellent affinity with spices and flavors, and reduces the content of surface oxygen groups, thereby improving hydrophobicity.
[0046] In one embodiment, the activated carbon fiber felt has a thickness of 1 to 3 mm and a density of 0.5 to 0.15 g / cm 3 , specific surface area 1000~1200m 2 / g, average pore size 1.5~2nm, water absorption pore volume 0.85~0.95cm 3 / g.
[0047] In one embodiment, the mass concentration of zinc chloride in the zinc chloride solution is 2-8%.
[0048] In one embodiment, the mass concentration of potassium hydroxide in the potassium hydroxide solution is 2-8%.
[0049] In one embodiment, the heat treatment temperature is 950-1200°C, and the heat treatment time is 2-4h. The inventors of the present invention have found that the heat treatment temperature is the key parameter of the present invention. By controlling the heat treatment temperature to 950-1200°C, it can not only promote the formation of a multi-level pore structure and increase the pore capacity, but also make the carbon fiber felt have a certain degree of graphene, improve the excellent affinity with spices and flavors, and remove the surface oxygen group content, inhibit the rapid desorption of spices and flavors, and improve the sustained release effect.
[0050] In one embodiment, the volume ratio of nitrogen to carbon dioxide is (80-95):(5-20).
[0051] In one embodiment, the volume ratio of nitrogen to hydrogen is (80-95):(5-20).
[0052] One embodiment of the present application provides an application of a porous carbon fiber felt in preparing a fragrance filter material.
[0053] An embodiment of the present application provides a fragrance material, including a porous carbon fiber felt and a fragrance loaded inside the porous carbon fiber felt, wherein the loading amount of the fragrance is 58 to 72 g / m 2 ;
[0054] The porous carbon fiber felt is the porous carbon fiber felt described above.
[0055] like Figure 1 As shown, an embodiment of the present application provides a fragrance, including a fragrance material and a coating 2 located on at least one surface of the fragrance material 1, wherein the coating includes an inorganic microporous material and a sol;
[0056] The solvent includes alumina sol or silica sol;
[0057] The inorganic microporous material includes at least one of 3A molecular sieve, 5A molecular sieve, X-type zeolite, ZSM series molecular sieve, 13X molecular sieve, activated carbon molecular sieve, and activated carbon fiber powder;
[0058] The fragrance material is the fragrance material described above.
[0059] The present invention arranges a coating on the surface of the fragrance material. The coating containing the inorganic microporous material can effectively capture the released fragrance molecules. The fragrance material can capture the released fragrance molecules for a second time, provide a buffer zone, effectively extend the rapid release cycle of the previous main body, and improve the service life.
[0060] Especially when 5A molecular sieve is used, the sustained-release effect is better.
[0061] In one embodiment, the coating has a thickness of 5 to 50 μm.
[0062] In one embodiment, the mass ratio of the inorganic microporous material to the sol is (1-20): (80-99).
[0063] like Figure 2 As shown, an embodiment of the present application provides a fragrance sustained-release product structure, including a filter element 2 and fragrance materials 1 located on both sides of the filter element, and the fragrance materials are the fragrance materials described above.
[0064] The present invention arranges the fragrance material on both sides of the filter element, which is not easy to fall off and can be perfectly integrated into the filter element system, and is easy to use.
[0065] Among them, the filter element mentioned in the present invention includes at least one of glass fiber for removing particulate matter, melt-blown filter element, carbon cloth filter element, household purifier activated carbon honeycomb filter element, fishing net sticky carbon filter element, and filter element in a heating, ventilation and air conditioning (HVAC) system.
[0066] The present invention is further described below with specific embodiments:
[0067] Example 1
[0068] A method for preparing a fragrance material comprises the following steps:
[0069] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0070] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1000 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0071] The active agent is composed of 5wt% potassium hydroxide (KOH) solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0072] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0073] Example 2
[0074] A method for preparing a fragrance material comprises the following steps:
[0075] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0076] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 950 °C for 2 h in a mixed atmosphere of nitrogen and carbon dioxide to obtain a porous carbon fiber felt;
[0077] The active agent is a 5wt% zinc chloride solution;
[0078] In the mixed atmosphere of nitrogen and carbon dioxide, the volume ratio of carbon dioxide is 20%;
[0079] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0080] Example 3
[0081] A method for preparing a fragrance material comprises the following steps:
[0082] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0083] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1100 °C for 2 h in a mixed atmosphere of nitrogen and hydrogen to obtain a porous carbon fiber felt;
[0084] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0085] In the mixed atmosphere of nitrogen and hydrogen, the volume ratio of hydrogen is 20%;
[0086] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0087] Example 4
[0088] A method for preparing a fragrance material comprises the following steps:
[0089] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0090] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1100 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0091] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0092] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0093] Example 5
[0094] A method for preparing a fragrance material comprises the following steps:
[0095] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0096] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 950 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0097] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0098] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40°C (to remove the essential oil with weak surface bonding) to obtain the fragrance material.
[0099] Example 6
[0100] A method for preparing a fragrance material comprises the following steps:
[0101] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0102] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1200 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0103] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0104] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0105] Example 7
[0106] A method for preparing a fragrance comprises the following steps:
[0107] Take the fragrance material of Example 1, mix 1g of inorganic microporous material with 10g of silica sol (30% SiO 2 ,7nm,360m 2 / g) are mixed evenly, and then the porous material surface is coated with a spray gun (0.5ml / min liquid spraying speed, spraying 10min, both the front and back sides are coated). Finally, it is naturally dried.
[0108] Comparative Example 1
[0109] The difference between Comparative Example 1 and Example 1 is that the activated carbon fiber felt is not treated.
[0110] A method for preparing a fragrance material comprises the following steps:
[0111] (1) Take a 20cm*20cm activated carbon fiber felt (thickness 2mm, density 0.1g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0112] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0113] Comparative Example 2
[0114] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 is processed under a carbon dioxide atmosphere.
[0115] A method for preparing a fragrance material comprises the following steps:
[0116] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0117] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1000 °C for 2 h in a carbon dioxide atmosphere to obtain a porous carbon fiber felt;
[0118] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0119] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0120] Comparative Example 3
[0121] The difference between Comparative Example 3 and Example 1 is that the activator in Comparative Example 3 is 10% hydrogen peroxide.
[0122] A method for preparing a fragrance material comprises the following steps:
[0123] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0124] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1000 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0125] The active agent is hydrogen peroxide;
[0126] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0127] Comparative Example 4
[0128] The difference between Comparative Example 4 and Example 1 is that the activator in Comparative Example 4 is 5 wt % potassium hydroxide solution.
[0129] A method for preparing a fragrance material comprises the following steps:
[0130] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0131] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1000 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0132] The active agent is a 5wt% KOH solution;
[0133] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0134] Comparative Example 5
[0135] The difference between Comparative Example 5 and Example 1 is that the heat treatment temperature is 850°C.
[0136] A method for preparing a fragrance material comprises the following steps:
[0137] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0138] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1000 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0139] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0140] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0141] Comparative Example 6
[0142] The difference between Comparative Example 6 and Example 1 is that the heat treatment temperature is 1300°C.
[0143] A method for preparing a fragrance material comprises the following steps:
[0144] (1) Preparation of porous carbon fiber felt: Take 20 cm*20 cm activated carbon fiber felt (thickness 2 mm, density 0.1 g / cm 3 , specific surface area 1100m 2 / g, average pore size 1.7~2nm, water absorption pore volume 0.89cm 3 / g);
[0145] The porous carbon fiber felt was added into 50 mL of activator, soaked for 3 h, dried in an oven at 100 °C, placed in a tube furnace, and heat treated at 1300 °C for 2 h in a nitrogen atmosphere to obtain a porous carbon fiber felt;
[0146] The active agent is composed of 5wt% KOH solution and 5wt% zinc chloride solution in a ratio of 1:1;
[0147] (2) Preparation of fragrance material: 3 g of sandalwood essential oil was evenly sprayed on the activated carbon fiber felt, left to stand for 4 h, and dried overnight at 40° C. (to remove the essential oil with weaker surface bonding) to obtain the fragrance material.
[0148] Test Example 1
[0149] The physical properties of the fragrance materials of the embodiments and comparative examples are shown in Table 1.
[0150] Pore size distribution structure according to ASTM UOP425-86N 2 Adsorption standard method test; air permeability test according to ASTMD737-18 standard. The surface oxygen-containing groups are tested by thermogravimetric analyzer to reduce the mass of thermal desorption in the range of room temperature to 1000 degrees (inert atmosphere such as N 2 ).
[0151] The amount of essential oil loaded can be calculated by the mass before and after loading (using a fine balance, which can be accurate to 0.001 mg).
[0152] Table 1 Essential oil adsorption, pore structure and surface chemical properties of porous activated carbon fiber materials in Examples and Comparative Examples
[0153]
[0154]
[0155] Test Example 2
[0156] The fragrance materials of the embodiment and the comparative example were respectively compounded with the automobile air conditioning filter element of the same size (placed at the rear end of the particle filter element), and then installed in the automobile air conditioning system, and the air conditioning was adjusted to the rated wind speed range (100m 3 / h). The running time is based on an average commuting time of 2 hours per day, and the car runs continuously for 1 hour each time. Calculated based on half a year, it runs continuously for 360 hours, and the weight change of the activated carbon fiber felt is tested over time.
[0157] The sensory test is to have 10 employees rate the fragrance in the car at different times, and then take the average value. 10 points means the fragrance is strong, 5 points means the fragrance is average, and 1 point means the fragrance is very bland.
[0158] Table 2 Fragrance sustained release rate, average service life and sensory evaluation results of porous activated carbon fiber-based fragrance materials in Examples and Comparative Examples
[0159]
[0160]
[0161] It can be seen from Table 2 that the porous carbon fiber felt of the present invention can effectively control the sustained release effect of spices and flavors, so that spices and flavors are released in a long-lasting and stable manner, and effectively improve the service life and use effect.
[0162] Test Example 2
[0163] According to the method of Example 7, different inorganic microporous materials were used for preparation (as shown in Table 3 for details), and the average sustained release rate and average life of the fragrance were tested according to the same method as in Test Example 1.
[0164] Unmodified in the table means that the porous carbon fiber felt is not treated in any way and is directly coated according to the method of Example 7.
[0165] Table 3 Fragrance sustained release rate and average service life of porous carbon fiber after surface coating modification
[0166] Coating materials <![CDATA[Average fragrance slow-release rate (g / m 2 / h)]]> Average life expectancy (months) No modification 0.215 4 3A molecular sieve 0.163 7 5A molecular sieve 0.169 7 ZeoliteX 0.180 6 ZSM-5 0.174 6.5 Zeolite 13X 0.181 6 Activated carbon molecular sieve 0.159 8 SBA-15 0.208 4.5
[0167] It can be seen that using microporous inorganic molecular sieves, zeolites or activated carbon molecular sieve materials (pore size of 0.3-1nm) to modify the surface coating of the fragrance ceramic plate can effectively slow down the release rate and thus extend the service life. However, the modification effect of using mesoporous materials (SBA-15) is not particularly significant.
[0168] Test Example 3
[0169] Approximately 30 microns
[0170] The method of Example 7 was adopted, and the inorganic microporous material was selected as X-type zeolite. The coating thickness was controlled by controlling the spraying amount. The coating thickness was tested by scanning electron microscopy to explore the effect of different thicknesses on the sustained release effect of the fragrance. Figure 3 shown.
[0171] It can be seen that for specific microporous materials, the coating thickness (5-60um) will also affect the sustained release rate. Generally, the thicker the coating thickness, the slower the release rate. However, the thicker the coating thickness, the more it will form a sealing layer, resulting in a less obvious aromatherapy effect. Therefore, the optimal thickness is 10-35μm.
[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A porous carbon fiber felt, characterized in that: The average pore size is 1-1.5 nm, and the total pore volume is 1-1.2 cm 3 / g, air permeability ≤8s, surface oxygen group content 0.6~2.1wt%; The porous carbon fiber felt has ultra-micropores, the pore size of the ultra-micropores is 0.3-1.2 nm, and the capacity of the ultra-micropores is 0.4-0.5 cm 3 / g.
2. The method for preparing the porous carbon fiber felt according to claim 1, characterized in that: The following steps are involved: The activated carbon fiber felt is immersed in an activator, dried, and heat-treated to obtain a porous carbon fiber felt; The activator comprises zinc chloride solution and potassium hydroxide solution; the mass ratio of the zinc chloride solution to the potassium hydroxide solution is 1:(0-1); The heat treatment is performed in a nitrogen atmosphere, a mixed atmosphere of nitrogen and carbon dioxide, or a mixed atmosphere of nitrogen and hydrogen.
3. The method for preparing porous carbon fiber felt according to claim 2, characterized in that: The thickness of the activated carbon fiber felt is 1-3 mm, and the density is 0.5-0.15 g / cm 3 , specific surface area 1000~1200m 2 / g, average pore size 1.5~2nm, water absorption pore volume 0.85~0.95cm 3 / g.
4. The method for preparing porous carbon fiber felt according to claim 2, characterized in that: The mass concentration of zinc chloride in the zinc chloride solution is 2-8%; and / or The mass concentration of potassium hydroxide in the potassium hydroxide solution is 2-8%.
5. The method for preparing porous carbon fiber felt according to claim 2, characterized in that: The heat treatment temperature is 950-1200° C., and the heat treatment time is 2-4 hours.
6. The method for preparing porous carbon fiber felt according to claim 2, characterized in that: The volume ratio of nitrogen to carbon dioxide is (80-95):(5-20); and / or The volume ratio of the nitrogen and hydrogen is (80-95):(5-20).
7. Use of the porous carbon fiber felt according to claim 1 in preparing fragrance.
8. A fragrance material, characterized in that: The porous carbon fiber felt comprises a flavor loaded inside the porous carbon fiber felt, wherein the loading amount of the flavor is 58 to 72 g / m 2 ; The porous carbon fiber felt is the porous carbon fiber felt according to claim 1.
9. A fragrance, comprising a fragrance material and a coating located on at least one surface of the fragrance material, wherein the coating comprises an inorganic microporous material and a sol; The solvent includes alumina sol or silica sol; The inorganic microporous material includes at least one of 3A molecular sieve, 5A molecular sieve, X-type zeolite, ZSM series molecular sieve, 13X molecular sieve, activated carbon molecular sieve, and activated carbon fiber powder; The fragrance material is the fragrance material according to claim 8.
10. The fragrance according to claim 9, characterized in that The mass ratio of the inorganic microporous material to the sol is (1-20):(80-99).
11. A fragrance, comprising a filter element and fragrance materials located on both sides of the filter element, wherein the fragrance materials are the fragrance materials according to claim 8.
